Importance And Implementation Of Nursing Documentation: Review Study - Alkouri, Osama A; AlKhatib, Ahed J; Kawafhah, Mariam (European Scientific Journal, ESJ, 2016)
This study was conducted to review the literature about nursing documentation. We presented the importance and implementation of nursing documentation. The importance of this topic has been realized here, in Jordan, and the Ministry of Health has recently started application of electronic documentation systems. Nursing documentation can be either paper based or electronic based documentation. Paper based documentation has been described not meet the required standards. We argued the standards of nursing documentation that should be met including completeness, clearing, and concision.